PENGARUH HERDING BEHAVIOR, OVERCONFIDENCE DAN RISK TOLERANCE TERHADAP KEPUTUSAN INVESTASI DENGAN FINANCIAL LITERACY SEBAGAI VARIABEL MODERASI: STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MUHAMMADIYAH SURAKARTA - Rahma Tusamma Salsabila; Atwal Arifin (LP2M Universitas Bina Bangsa, 2024)
The global economic crisis due to the Covid-19 outbreak has had an impact on the Indonesian economy. One of the efforts to recover the economy is investment activities. The recent increase in the number of investors must be accompanied by awareness of other risks and losses. Therefore, investors must have the ability to consider organized financial decisions. Considerations in investment decisions are also based on psychological factors of bias and emotions of investors. This study aims to analyze and examine the effect of herding behavior, overconfidence, and risk tolerance on investment decisions moderated by Financial literacy. The population in this study is students of the Faculty of Economics and Business, University of Muhammadiyah Surakarta. The method in this study is quantitative using surveys with questionnaires. The sampling technique used is convenience sampling technique. The data analysis used used multiple linear regression analysis and Moderated Regression Analysis using SPSS version 25. The results of this study show that herding behavior, overconfidence and risk tolerance have a positive and significant influence on investment decisions. Financial literacy cannot moderate the relationship between herding behavior, overconfidence and risk tolerance